Deepfake Detection Using Machine Learning Techniques: A Scalable Solution for Media Integrity - Pratik Godase,; Sanket Pawar,; Rohan Dhengale,; Shavarsiddha Gurav,; Avinash Kapare, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The proliferation of deepfake technology has  introduced unprecedented challenges to media integrity and public trust. Leveraging advanced machine learning techniques, this study proposes a scalable solution for detecting deepfake content in digital media. Our methodology employs convolutional neural networks (CNNs) to capture spatial inconsistencies and recurrent neural networks (RNNs) to analyze temporal patterns in video data, ensuring comprehensive detection capabilities. Utilizing publicly available deepfake datasets, the proposed framework demonstrates high accuracy and robustness against various forgery methods. The results highlight the model's potential to address real-world challenges, offering a reliable approach to identifying manipulated content across diverse platforms. This research not only contributes to the growing field of deepfake detection but also underscores the critical role of scalable and adaptable solutions in combating the misuse of AI-generated media. Future work will focus on enhancing model generalization across emerging deepfake generation techniques.
Keywords: Deepfake Detection; Machine Learning; Media Integrity; Convolutional Neural Networks; Temporal Analysis